Navigating Environmental Threats to New Ventures: A Regulatory Fit Approach to Bricolage - Adomako, Samuel; Zhu, Fei; Hsu, Dan K.; Istipliler, Baris; Wiklund, Johan (Journal of Management Studies, 2025)
Bricolage is a critical strategy used by entrepreneurs to generate resources for new ventures in response to environmental threats that result in resource constraints. However, inconsistent findings exist. Whereas the predominant view in the bricolage literature suggests that resource‐constrained or threatening environments motivate new ventures to bricolage to survive and thrive, some empirical evidence shows that some firms choose not to bricolage in such environments. This paper addresses the inconsistent findings by integrating regulatory fit theory with the bricolage literature, arguing that the effect of environmental threat on bricolage depends on entrepreneurs' dispositional regulatory focus. Data from a time‐lagged survey of 396 Taiwanese entrepreneurs support our hypotheses. Our findings suggest that promotion (prevention) focus disposition is positively (negatively) related to bricolage. More importantly, both promotion and prevention foci weaken the effect of environmental threat on bricolage, serving as boundary conditions for this relationship. Finally, our additional analysis reveals gender differences in bricolage and the contingent effect of promotion focus disposition, enabling us to contribute to regulatory fit theory.